2010
DOI: 10.1007/s12665-010-0794-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spatial fracture intensity as a control on flow in fractured rock

Abstract: Spatial fracture intensity (P 32 , fracture area by volume) is an important characteristic of a jointed rock mass. Although it can hardly ever be measured, P 32 can be modeled based on available geological information such as spatial data of the fracture network. Flow in a mass composed of low-permeability hard rock is controlled by joints and fractures. In this article, models were developed from a geological data set of fractured andesite in LanYu Island (Taiwan) where a site is investigated for possible dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Wide aperture fractures and high fracture densities commonly correlate to permeable zones in geothermal wells [ Barton et al ., ; Sheridan and Hickman , ; McLean and McNamara , ; Wallis et al ., ; Co , ]. Fracture length and connectivity, their interrelationship, and the relationship between these factors and fracture aperture and density are also important when considering structural permeability in geothermal reservoirs [ Long and Witherspoon , ; Lee et al ., ; Barton et al ., ]. Increased connectivity and density of a fracture network in a reservoir will often allow for higher permeability associated with the presence of longer fractures (in turn associated with wider apertures) [ Long and Witherspoon , ; Gudmundsson et al ., ; Philipp et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Wide aperture fractures and high fracture densities commonly correlate to permeable zones in geothermal wells [ Barton et al ., ; Sheridan and Hickman , ; McLean and McNamara , ; Wallis et al ., ; Co , ]. Fracture length and connectivity, their interrelationship, and the relationship between these factors and fracture aperture and density are also important when considering structural permeability in geothermal reservoirs [ Long and Witherspoon , ; Lee et al ., ; Barton et al ., ]. Increased connectivity and density of a fracture network in a reservoir will often allow for higher permeability associated with the presence of longer fractures (in turn associated with wider apertures) [ Long and Witherspoon , ; Gudmundsson et al ., ; Philipp et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Lapponi et al (2011) used outcrop data to construct a 3D model in a dolomitized carbonate reservoir rock from the Zagros Mountains, southwest Iran. Lee et al (2011) studied the spatial fracture intensity effect on hydraulic flow in fractured rock. They used outcrop for simulation of spatial fracture intensity distribution.…”
Section: Fracture Simulation Methods For Carbonate Rocksmentioning
confidence: 99%
“…This formation is impermeable and about 1 This unit outcrops at the reservoir area and downstream side of the Mut dam site. boreholes showed that this formation has a thickness of approximately 40-50 m alo Regression analyses as statistical methods are widely used in geotechnical and rock engineering practice (e.g., Hoek and Brown [27]; Apte et al [28]; Akca [29]; Uddameri [30]; Sivrikaya [31]; Zorlu et al [32]; Yagiz et al [33]; Yagiz and Gokceoglu [34]; Chen-Chang et al [35]; Valia and Arpa, [36]; Azimian and Ajalloeian R [10]; Farid and Rizwan [15]; Öge and Çırak [37]; Rahimi et al [38]). Average values of rock mass properties of karstic limestone block (Q value, RQD, GSI, JSP, Ap, Lu, SPI, k) and average Gt were calculated (Table 9).…”
Section: Simple and Multiple Regression Analysesmentioning
confidence: 99%
“…Function modellings were performed according to equations derived with a simple regression equation and the results of the multiple nonlinear regression analyses are given in Table 12. Considering the VAF, RMSE, R 2 , and MAPE values, Equations (17), (20), (23), (27), (28)-(30), (34), and (35) show the better prediction. Remaining empirical equations also exhibit significant performances.…”
mentioning
confidence: 99%
See 1 more Smart Citation